Some aspects of tuberculous meningitis - Taslim S. Soetomenggolo (Paediatrica Indonesiana, 1999)
Tuberculous meningitis remains a serious pediatric problem in Indonesia; the morbidity, mortality, and sequelae are still high. During January 1994 and December 1998 had been hospitalized 85 patients of tuberculous meningitis. The diagnosis was based on the clinical signs & symptoms, the abnormalities of cerebrospinal fluid, the tuberculin skin test, and the imaging of chest & brain. The sex distribution was male patients more than female patients. The age distribution was between 5 months and 11 years, and most of the patients were at the age of less than 5 years old (77.6%). Most of the patients (65.9%) suffered from undernutrition. On admission only 7 patients (8.2%) were in the stage I, and most of the patients (91.8%) were in the stage U and m. The most frequent clinical signs & symptoms of the patients were fever, unconsciousness, paresis of extremities, nuchal rigidity, convulsions, and cranial nerve palsies. The cerebrospinal fluid showed pleocytosis, and most of the cells were lymphocytic type. Only 36.5% of the patients showed positive tuberculin skin test, and 16.5% of the 85 patients had received BCG vaccination. The chest X-ray examination showed miliary tuberculosis in 24.7% of the patients, and other abnormalities in 36.5%. Head CT-scan examination showed ventriculomegaly in 75.9%, tuberculomas in 6.9%, brain infarcts in 3.4%, meningoencephalitis in 3.4%, and brain atrophy in 5.2% of the patients. The mortality of this study was 14.1%.